PENDIDIKAN KECAKAPAN HIDUP PADA REMAJA MASYARAKAT BAJO DESA SOROPIA, KONAWE - Herman Herman (Institut Agama Islam Negeri Kendari, 2017)
This study aims to investigate the teenagers’ life of Bajo society in Bokori of Soropia, Konawe related to their life skill education. The results reveal that (1) the Bokori community in Soropia Konawe is generally very enthusiastic about the life skill the teenagers in this village. According to them, life education is very important because with these skills, they will be able to support the future and to solve and overcome the problems they face in life. (2) the implementation of life skills education for teenagers in Bokori is good enough. It is seen from the efforts made by parents who accustom their children to work from the early age, teach their children working theory and practice, and motivate them. In the implementation of the life skill education, there are several supportive factors, namely the existence of a network and cooperation with people and institutions that exist in Soropia, and their teachers are professionals. In addition, in the implementation of life skill education, there are also some obstacles, namely financial factors or funding which is the most important factor, lack of facilities and infrastructure, lazy teenagers, and limited time allocation. The efforts undertaken to overcome these obstacle are establishing the relationship and cooperation with the people and institutions that schools and offices, developing tolerance and guidance to teenagers, and maximizing existing activities. Unfortunately, most of teenagers prefer to work as sailorman because of the higher income that a handyman salary